Pengaruh Budaya Organisasi, Efektivitas Pengendalian Internal, Kesesuaian Kompensasi Terhadap Kecenderungan Kecurangan Akuntansi Pada Lembaga Perkreditan Desa (LPD) Se-Kecamatan Mengwi - Dewi, Desak Putu Putri Laksmi; Yuniasih, Ni Wayan; Padnyawati, Kadek Dewi (Hita Akuntansi dan Keuangan, 2025)
The partiality for bookkeeping compulsion has made in every aspect of the planet, including Indonesia, whose defilement record arranging was in 107th situation out of 175 nations on the planet in 2014. The propensity for pressure is affected by the presence or nonappearance of legitimization or protect. Legitimization is the chance of the presence of an opening in a representative's own unique uprightness or other moral thinking. This evaluation desires to finish up the impact of Different evened out Culture, Sensibility of Inner Control, Reasonableness of Pay on the Liking of Bookkeeping Extortion around Credit Affiliations (LPD) in Mengwi Region. Everybody in this study is all LPDs in Mengwi Region, adding up to 38 LPDs with 306 workers. How much tests in this study was 109 individuals who were settled utilizing a purposive taking a gander at framework and had a go at utilizing different direct lose the faith evaluation strategies. The results of this appraisal show that genuine culture impacts the inclination for bookkeeping shakedown. The common sense of inward control impacts the liking for bookkeeping twisting. Reasonableness of remuneration authoritatively impacts the inclination for bookkeeping double dealing. The consequences of this evaluation can be utilized as thought in organizing rules and plans related with endeavors to diminish the propensity for bookkeeping duplicity.